Hippobutenolides A and B, two new long-chain fatty acid esters from the marine sponge Hippospongia lachne. (9th November 2021) - Hong, Li-Li; Wang, Jie; Liu, Li-Yun; Sun, Fan; Sun, Jia-Bao; Miao, Xian-Xian; Liu, Hong-Yan; Zhan, Kai-Xuan; Jiao, Wei-Hua; Lin, Hou-Wen
Graphical abstract: Abstract: Two new fatty acid esters, hippobutenolides A (1 ) and B (2 ), featuring a long linear aliphatic chain attached to a butanolide residue, together with two known related ones (3 and 4 ), were isolated from the marine sponge Hippospongia lachne . The structures of all compounds were determined by extensive spectroscopic analysis and modified Mosher's method. All isolates were evaluated for cytotoxicity against three non-small cell lung cancer (NSCLC) cells (A549, PC9, and HCC827) as well as one cisplatin-resistant NSCLC cell (A549-DDP) and two gefitinib-resistant NSCLC cells (PC9-GR and HCC827-GR). Compound 3 displayed cytotoxicity against all cell lines with IC50 values ranging from 18.86 to 33.24 μM.